Females in print advertisements: the cultural stance - Lim, Li Yin; Lee, Siew Chin (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2020)
The visual imagery provided by the advertisements can tell powerful stories of our attitudes, values, beliefs and behaviours through meanings and associations. Scholars advocated the view that language of advertising not only conveys information about the product but also cultural values. In advertisements, women are often used as baits to attract customers’ attention. Media is gendered, displaying specific trends and patterns associated with the female gender. Thus, in media, women are portrayed in diverse roles in positions of power, yet also exploited in positions of inequality; from household chores, to objects of sexual desire. Hence, the research question of “What roles are ascribed to the female gender in print advertisements?” This research aims to explore 1) the roles of female in digital print advertisements; and 2) the meaning-makings through representation of these females. Eight print advertisements are purposely selected for this study. In the findings, females are associated with: feminine touch, physical lowering, function ranking, licensed withdrawal and ritualization of subordination.